Physicochemical stability study of a biosimilar of Bevacizumab in vials and after dilution in 0.9% NaCl in polyolefin intravenous bags - Vieillard Victoire; Paul Muriel (De Gruyter, 2023)
Bevacizumab was first marketed in 2005. Since then, its stability has been extensively studied. The arrival of numerous biosimilars on the market has called into question these stabilities and organisation within reconstitution units. To study the stability of the Bevacizumab biosimilar Alymsys® marketed by Zentiva laboratory in ready-to-use vials at a concentration of 25 mg/mL and following dilution to obtain final concentrations of 1.4 and 16.5 mg/mL and storage in polyolefin IV bags at 4 °C. In parallel, the impact of a storage temperature excursion at 25 °C for three days and storage of the vial before opening at room temperature (25 ± 2 °C) and after opening at 4 °C was studied.